Radical Relations : Lesbian Mothers, Gay Fathers, and Their Children in the United States since World War II - Rivers, Daniel Winunwe (Book collections on Project MUSE., 2013)
In Radical Relations, Daniel Winunwe Rivers offers a previously untold story of the American family: the first history of lesbian and gay parents and their children in the United States. Beginning in the postwar era, a period marked by both intense repression and dynamic change for lesbians and gay men, Rivers argues that by forging new kinds of family and childrearing relations, gay and lesbian parents have successfully challenged legal and cultural definitions of family as heterosexual. These efforts have paved the way for the contemporary focus on family and domestic rights in lesbia.